2005
DOI: 10.1038/sj.emboj.7600550
|View full text |Cite
|
Sign up to set email alerts
|

The DEAD box protein p68: a novel transcriptional coactivator of the p53 tumour suppressor

Abstract: The DEAD box RNA helicase, p68, has been implicated in various cellular processes and has been shown to possess transcriptional coactivator function. Here, we show that p68 potently synergises with the p53 tumour suppressor protein to stimulate transcription from p53-dependent promoters and that endogenous p68 and p53 co-immunoprecipitate from nuclear extracts. Strikingly, RNAi suppression of p68 inhibits p53 target gene expression in response to DNA damage, as well as p53-dependent apoptosis, but does not inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
217
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(235 citation statements)
references
References 37 publications
13
217
1
2
Order By: Relevance
“…This is the case of the highly related ddx5 and ddx17 RNA helicases (also known as p68 and p72, respectively) that act both in transcription and splicing. Indeed, ddx5 and ddx17 are transcriptional coregulators of the estrogen receptor alpha, p53, betacatenin and MyoD transcription factors among others (Watanabe et al, 2001;Bates et al, 2005;Caretti et al, 2006;Fuller-Pace and Ali, 2008). It is believed that ddx5 and ddx17 are recruited on target gene promoters by these transcriptional factors and in turn recruit the RNA polymerase II or enzymes with histone acetylase or deacetylase activities (Metivier et al, 2003;Rossow and Janknecht, 2003;Wilson et al, 2004;Janknecht, 2010;Dutertre et al, 2010a;Fuller-Pace and Moore, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the case of the highly related ddx5 and ddx17 RNA helicases (also known as p68 and p72, respectively) that act both in transcription and splicing. Indeed, ddx5 and ddx17 are transcriptional coregulators of the estrogen receptor alpha, p53, betacatenin and MyoD transcription factors among others (Watanabe et al, 2001;Bates et al, 2005;Caretti et al, 2006;Fuller-Pace and Ali, 2008). It is believed that ddx5 and ddx17 are recruited on target gene promoters by these transcriptional factors and in turn recruit the RNA polymerase II or enzymes with histone acetylase or deacetylase activities (Metivier et al, 2003;Rossow and Janknecht, 2003;Wilson et al, 2004;Janknecht, 2010;Dutertre et al, 2010a;Fuller-Pace and Moore, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, on one hand, as transcriptional coactivators of estrogen receptor alpha, they may contribute to the proliferative effect of estradiol on breast cancer cells (Wortham et al, 2009;Dutertre et al, 2010a) and, as coregulators of betacatenin, they may contribute to the epithelial to mesenchymal transition, which has been associated with breast cancer progression (Yang et al, 2006). On the other hand, as coactivators of p53 and Smad, ddx5/ ddx17 may exert tumor suppressor functions (Warner et al, 2004;Bates et al, 2005). However, oncogenic functions or tumor suppressor roles of ddx5 and ddx17 are still a matter of debate and could be contextdependent (Fuller-Pace and Moore, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The sequence of the flanking genomic DNA indicated that CB02119 was inserted within an intron of Rm62 (Fig. 1B), the Drosophila ortholog of the p68 RNA helicase, a protein that in mammals functions in RNA processing (Bates et al 2005;Lin et al 2005). Multiple differentially spliced transcripts of this gene encode proteins of ∌63 kDa as well as one isoform of 79 kDa ( Fig.…”
Section: Drosophila P68 Is Found At Sites Of Active Trancriptionmentioning
confidence: 99%
“…Genes lacking introns such as hsp70 were affected in the same manner as intron-containing genes. Second, mammalian P68 has been implicated as a direct transcriptional regulator, and may participate in activating p53 target genes (Bates et al 2005). …”
Section: P68 Is Required For Transcriptional Deactivationmentioning
confidence: 99%
“…Subsequently, p68 was found to stimulate transcriptional activation mediated by CBP/p300 (Rossow and Janknecht, 2003). We have previously demonstrated that p68 is a transcriptional coactivator of the tumor suppressor p53 and is important for the p53 DNA damage response (Bates et al, 2005) and that, in some contexts, it can act as a transcriptional repressor (Wilson et al, 2004). Recently, p68 was shown to coactivate MyoD and to act as a coregulator of skeletal muscle differentiation (Caretti et al, 2007).…”
Section: Introductionmentioning
confidence: 99%